Damage identification on impact and lightning damage of flax composite laminates (Linum usitatissimum) using long-pulse thermography of a low-resolution infrared camera - Anwar, Murniwati; Mustapha, Faizal; Hameed Sultan, Mohamed Thariq; Abdul Halin, Izhal; Abdullah, Mohd Na'im; Hassim, Mohamad Iswady; Mustapha, Mazli (Frontiers Media, 2021)
The demand for composite fiber material is significantly high due to its excellent mechanical properties and its use in various industries. Recently, with the increasing awareness of environmental issues, researchers are now focusing more on eco-friendly and green materials. A biocomposite offers a good balance of strength and stiffness ratio, bending and membrane mechanical properties, balanced thermal distortion stability, reduced weight and cost, improved fatigue resistance, reduced notch sensitivity, and, comparatively, better performance than synthetic composites. Yet, due to the complex anisotropy of the composite material, the inspection and detection of inner defects become a challenge. Long-pulse thermography is one of the non-destructive evaluations (NDEs) used to detect defects in composite materials. However, very limited research has been carried out on the usage of a low-resolution infrared camera to perform defect or damage inspection on flax composite laminates. In this paper, an experimental setup of a long pulse thermography system using low-resolution infrared camera was performed on flax bio-composite to identify impact and lightning damage. The result highlights that with control parameters, a low-resolution infrared camera has the capability to capture the lightning and impact defects of flax biocomposites using the long-pulse thermography system. An image processing method is then applied to the defect to improve the quality of defect detection and reduce background noise.